The Acts of the Apostles: A Hypertextual Commentary - Adamczewski, Bartosz (European Studies in Theology, Philosophy and History of Religions Series, 2023)
"This monograph demonstrates that the Acts of the Apostles is a result of highly creative, hypertextual reworking of the Letter to the Galatians. This detailed reworking consists of over 500 strictly sequentially organized conceptual, and at times also linguistic correspondences between Acts and Galatians. The strictly sequential, hypertextual dependence on Galatians explains numerous surprising features of Acts. Critical explanations of such features, which are offered in this monograph, ensure the reliability of the new solution to the problem of the relationship between Acts and the Pauline and post-Pauline letters"--